Observation of Main‐Group Tricarbonyls [B(CO)3] and [C(CO)3]+ Featuring a Tilted One‐Electron Donor Carbonyl Ligand. Issue 7 (15th January 2016) - Jian, Jiwen; Jin, Jiaye; Qu, Hui; Lin, Hailu; Chen, Mohua; Wang, Guanjun; Zhou, Mingfei; Andrada, Diego M.; Hermann, Markus; Frenking, Gernot
Abstract: A combined experimental and theoretical study on the main‐group tricarbonyls [B(CO)3 ] in solid noble‐gas matrices and [C(CO)3 ] + in the gas phase is presented. The molecules are identified by comparing the experimental and theoretical IR spectra and the vibrational shifts of nuclear isotopes. Quantum chemical ab initio studies suggest that the two isoelectronic species possess a tilted η 1 (μ1 ‐CO)‐bonded carbonyl ligand, which serves as an unprecedented one‐electron donor ligand. Thus, the central atoms in both complexes still retain an 8‐electron configuration. A thorough analysis of the bonding situation gives quantitative information about the donor and acceptor properties of the different carbonyl ligands. The linearly bonded CO ligands are classical two‐electron donors that display classical σ‐donation and π‐back‐donation following the Dewar–Chatt–Duncanson model. The tilted CO ligand is a formal one‐electron donor that is bonded by σ‐donation and π‐back‐donation that involves the singly occupied orbital of the radical fragments [B(CO)2 ] and [C(CO)2 ] + . Abstract : A combined experimental and theoretical study on the main‐group tricarbonyls [B(CO)3 ] and [C(CO)3 ] + is presented. The molecules are identified by comparing experimental and theoretical IR spectra and vibrational shifts of nuclear isotopes. Quantum chemical ab initio studies suggest that the two isoelectronic species possess a tilted η 1 (μ1 ‐CO)‐bonded carbonyl ligand, which serves as an unprecedented one‐electron donor ligand.